Photogrammetric Maps of a Volcanic Eruption Area, Deception Island, Antarctica - Brecher, Henry H. (Research Foundation and the Institute of Polar Studies, The Ohio State University, 1975)
On cover: "RF 3861." The volcanic Deception Island, Antarctica, has erupted three times since 1967. Three maps are presented which display topographic changes of the most affected part of the island. The fourth map represents a crater in the terminus of a cirque glacier which has been recently examined. Procedures used in preparing the maps are discussed. Office of Polar Programs, National Science Foundation, Grant No. GV-41368.